2016
DOI: 10.1007/s00441-016-2514-7
|View full text |Cite
|
Sign up to set email alerts
|

Content of testis-specific isoform of Na/K-ATPase (ATP1A4) is increased during bovine sperm capacitation through translation in mitochondrial ribosomes

Abstract: Capacitation comprises a series of structural and functional modifications of sperm that confer fertilizing ability. We previously reported that the testis-specific isoform of Na/K-ATPase (ATP1A4) regulated bovine sperm capacitation through signaling mechanisms involving kinases. During subsequent investigations to elucidate mechanisms by which ATP1A4 regulates sperm capacitation, we observed that ATP1A4 was localised in both raft and non-raft fractions of the sperm plasma membrane and that its total content w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 75 publications
3
28
0
Order By: Relevance
“…We previously noted an increase in the content of ATP1A4 during capacitation, which was attributed to mitochondrial translation of ATP1A4 mRNA (Rajamanickam et al, 2017); a similar mechanism is likely responsible for ATP1A1 production during capacitation. Despite this increase in protein content in membrane fractions, ATP1A4 and ATP1A1 enzyme activity was lower in the raft fraction compared to the non-raft fraction.…”
Section: Figurementioning
confidence: 83%
See 3 more Smart Citations
“…We previously noted an increase in the content of ATP1A4 during capacitation, which was attributed to mitochondrial translation of ATP1A4 mRNA (Rajamanickam et al, 2017); a similar mechanism is likely responsible for ATP1A1 production during capacitation. Despite this increase in protein content in membrane fractions, ATP1A4 and ATP1A1 enzyme activity was lower in the raft fraction compared to the non-raft fraction.…”
Section: Figurementioning
confidence: 83%
“…We used a non‐detergent (sodium carbonate)‐based approach to separate raft and non‐raft domains, followed by biochemical characterization, as previously reported (Asano et al, ; Rajamanickam et al, ). The non‐raft marker α‐tubulin (Asano et al, ; Cross, ) confirmed the purity of the membrane fractions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since mature spermatozoa are thought to be transcriptionally and translationally silent, the increase in NKAα4 at the plasma membrane could be due to translocation of the protein from intracellular compartments to the sperm surface. Alternatively, in bull sperm, it has been shown that NKAα4 increase can take place by mitochondrial ribosome-associated translation [ 85 ]. We are currently performing additional experiments to ascertain the location and molecular mechanisms involved in the subcellular translocation of NKAα4 in mouse and human sperm.…”
Section: Nkaα4 Function During Sperm Capacitationmentioning
confidence: 99%